2017
DOI: 10.3171/2017.2.focus16539
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for touch-free patient registration for robot-assisted intracranial surgery: application accuracy from a phantom study and a retrospective surgical series

Abstract: OBJECTIVEThe purpose of this study was to compare the accuracy of Neurolocate frameless registration system and frame-based registration for robotic stereoelectroencephalography (SEEG).METHODSThe authors performed a 40-trajectory phantom laboratory study and a 127-trajectory retrospective analysis of a surgical series. The laboratory study was aimed at testing the noninferiority of the Neurolocate system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 23 publications
1
43
1
2
Order By: Relevance
“…More recently, the method has gained popularity in centers outside Europe, earning worldwide clinical application . It has been demonstrated that the SEEG methodology enables precise recordings from deep cortical and subcortical structures, in multiple noncontiguous lobes, allowing bihemispheric explorations while avoiding the need for large craniotomies . One of the main advantages of the SEEG method is the ability to achieve superior implantation accuracy in comparison to other methods of invasive monitoring, without direct visualization of the cerebral cortex via an open craniotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the method has gained popularity in centers outside Europe, earning worldwide clinical application . It has been demonstrated that the SEEG methodology enables precise recordings from deep cortical and subcortical structures, in multiple noncontiguous lobes, allowing bihemispheric explorations while avoiding the need for large craniotomies . One of the main advantages of the SEEG method is the ability to achieve superior implantation accuracy in comparison to other methods of invasive monitoring, without direct visualization of the cerebral cortex via an open craniotomy.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 It has been demonstrated that the SEEG methodology enables precise recordings from deep cortical and subcortical structures, in multiple noncontiguous lobes, allowing bihemispheric explorations while avoiding the need for large craniotomies. [9][10][11][12][13][14][15] One of the main advantages of the SEEG method is the ability to achieve superior implantation accuracy in comparison to other methods of invasive monitoring, without direct visualization of the cerebral cortex via an open craniotomy. This is in part related to (1) the applied stereotactic guiding device, (2) the type of stereotactic registration, and (3) the depth electrode implantation technique.…”
Section: Introductionmentioning
confidence: 99%
“…In frameless stereotaxy effects from brain shift, drill bending, image‐to‐patient registration techniques and differences in patient position make a large contribution to the overall accuracy of the application. Some of these errors can be reduced by intraoperative imaging. Furthermore, in their study, Mascott et al .…”
Section: Discussionmentioning
confidence: 99%
“…23 In frameless stereotaxy effects from brain shift, drill bending, image-to-patient registration techniques and differences in patient position 24 make a large contribution to the overall accuracy of the application. Some of these errors can be reduced by intraoperative imaging 4,5,25 . Furthermore, in their study, Mascott et al have reported that only implanted cranial fiducials have a statistically significant accuracy advantage over other registration techniques in frameless stereotaxy.…”
Section: Introductionmentioning
confidence: 99%
“…61 Other centres have incorporated stereo EEG into a neurorobotic surgical system with comparable results. 62,63 High-frequency oscillations are a potential marker for epileptogenicity and a predictive factor for positive epilepsy surgery outcomes. 64 A meta-analysis has shown a small but significant relationship between the removal of the highfrequency oscillation-generating brain region and favourable outcomes.…”
Section: Recent Advances In Epilepsy Monitoring and Surgerymentioning
confidence: 99%